2022
DOI: 10.21511/im.18(2).2022.10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consumers’ purchase intention to buy smartphones online

Abstract: In this technological era, online business is expanding due to increased internet conveniences. Smartphone users are drastically growing in Bangladesh, where it plays a vital role as a strong catalyst for economic development. On the other hand, the success of the online business is associated with creating online purchase tendency by determining influencing factors of consumers’ intention. The ultimate purpose of this paper is to identify the influential variables of consumers’ purchase intention to buy smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In many other countries, several similar studies were conducted in the same vein from different perspectives. In Bangladesh, Ali, Karim [ 39 ] found out that five variables were found significant in this buying behavior, namely Brand trust, reference group, service quality, reasonable price, and perceived usefulness. In Oman, Belwal, Hoque [ 40 ] found that students’ preferences for smartphones changed over time, not only for brands but also for the way they used these products and their related services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In many other countries, several similar studies were conducted in the same vein from different perspectives. In Bangladesh, Ali, Karim [ 39 ] found out that five variables were found significant in this buying behavior, namely Brand trust, reference group, service quality, reasonable price, and perceived usefulness. In Oman, Belwal, Hoque [ 40 ] found that students’ preferences for smartphones changed over time, not only for brands but also for the way they used these products and their related services.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Bringula, Moraga [ 38 ] USA Trust, purchase experience, and capability. Ali, Karim [ 39 ] Bangladesh Brand trust, reference group, service quality, reasonable price, and perceived usefulness. Castillo, Flores [ 41 ] Filipino Product brand and brand equity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have underscored the pivotal role of financial literacy in promoting economic growth, stability, and financial inclusion. In the global context, researchers such as (Alhassan, & Islam, 2021b;Ali et al, 2020;Ali et al, 2021;Ali et al, 2022) emphasize the positive correlation between financial literacy and effective risk management within financial institutions. Similarly, Abbas et al (2021) stress the significance of financial literacy in facilitating ethical decision-making among financial professionals, thereby enhancing public trust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sukuk presents a feasible alternative to conventional bonds, appealing to investors searching for halal investment opportunities while simultaneously guaranteeing competitive financial yields (Nagano, 2016). Bangladesh, characterized by a substantial Muslim populace and a burgeoning economy, offers a distinctive setting for investigating the purchase intention of Sharia-compliant Sukuk bonds (Rahaman et al, 2022;Akhter et al, 2022;Ali et al, 2022). The nation has experienced a notable increase in interest in Islamic finance and has implemented significant measures to foster its growth.…”
Section: Introductionmentioning
confidence: 99%